A New Evidence Combination Method Based on Consistent Strength - Changming Qiao; Shuli Sun (Institute of Advanced Engineering and Science, 2013)
A lot of practical applications show that DS (Dempster-Shafer) theory of evidence cannot deal with highly conflicted evidence. For this problem, Murphy proposed a method to solve it by modifying source model of evidence. But this method just calculated the mean of the conflicted evidence and didn’t pay much attention on their correlation. Based on the combination method of Murphy, a new method to calculate the weighted average of the conflicted evidence using consistent strength is proposed by taking the correlation into account. The proposed combination method can combine highly conflicted evidences to be more satisfactory. A numerical example shows the effectiveness of the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3585